القانون الواجب التطبيق على عقود التجارة الدولية - العماوي، إيهاب محمد سعيد محمود عويضه Alamawi, Ihab Mohammed Said Mahmoud Owaidah; عبدالعزيز، محمود لطفي محمود Abdulaziz, Mahmoud Lutfi Mahmoud; زاهر، مينا عادل Zaher, Mina Adel (جامعة القاهرة - كلية الحقوق - فرع الخرطوم, 2022)
في ظل تطور التجارة الدولية وأدواتها نتيجة الثورة التكنولوجية والمعرفية وتقدم وسائل الاتصال، أصبحت هناك صعوبات قانونية تعزى العقود التجارية الدولية نتيجة عدم ملائمة تطبيق منهج قاعدة التنازع في مجال العقود الدولية وبخاصة عقود التجارة الإلكترونية فيما يتعلق بالاختصاص القانوني، حيث تقوم فكرة تحديد القانون الواجب التطبيق على عقود التجارة الدولية على البحث عن القانون الأكثر ملائمة الذي يطبق على النزاع. وقد أخذ هذا المجال اهتمام فقه القانون الدولي الخاص في محاولة لإيجاد حلول لمشكلة تنازع القوانين من أجل تحديد القانون الواجب التطبيق، حيث أثير ذلك في ظل قانون الإرادة وتعبير الأطراف المتعاقدة عن تحديد القانون الواجب التطبيق سواء بشكل ضمني أو صريح، أو في حال غياب الإرادة من خلال الإسناد الموضوعي والمادي، كما أن التنظيم الدولي بذل جهودا كبيرة من أجل توحيد القوانين واستخراج نماذج يمكن الاهتداء بها في التشريعات الوطنية سواء كانت في شكل اتفاقي أو من خلال القوانين النموذجية وغيرها، وبيان مدى تطبيق تلك الاتفاقيات في التشريعات المختلفة وبخاصة في أوروبا والتشريع المصري. In light of the development of international trade and its tools as a result of the technological and knowledge revolution and the advancement of the means of communication, there have become legal difficulties in international commercial contracts as a result of the inadequacy of the application of the dispute rule approach in the field of international contracts, especially electronic commerce contracts with regard to legal jurisdiction, where the idea of determining the applicable law is based on International trade contracts to search for the most appropriate law applied to the dispute. This field has taken an interest in the jurisprudence of international law in an attempt to find solutions to the problem of conflict of laws in order to determine the applicable law, as this was raised under the law of will and the contracting parties ’expression of defining the applicable law, either implicitly or explicitly, or in the absence of the will from Through the objective and material attribution, the international organization has made great efforts to unify laws and extract models that can be guided in national legislation, whether in the form of an agreement or through model laws and others, and to show the extent of application of these agreements in various legislations, especially in Europe and Egyptian legislation.
Keywords: العقود التجارية -- التجارة الدولية -- القوانين والتشريعات -- التحكيم التجاري